Frost Tolerance of Acacia Tortilis Seedlings - Kackar, N L; Solanki, K R; Jindal, S K (Annals of Arid Zone, 2016)
Five hundred and four Six month old established plants raised from the seed of twelve different trees of Acacia torti/is were screened against frost attack at Jodhpur. Progenies of AT 11 showed resistance whereas of AT 3 and AT 12 trees showhed susceptibility to frost. Plants with approximately one meter height either escaped from the attack or were only partially affected.